Detection of methylation, acetylation and glycosylation of protein residues by monitoring 13C chemical-shift changes: A quantum-chemical study - Garay, Pablo Germán (2016)
Post-translational modifications of proteins expand the diversity of the proteome by several orders of magnitude and have a profound effect on several biological processes. Their detection by experimental methods is not free of limitations such as the amount of sample needed or the use of destructive procedures to obtain the sample. Certainly, new approaches are needed and, therefore, we explore here the feasibility of using 13C chemical shifts of different nuclei to detect methylation, acetylation and glycosylation of protein residues by monitoring the deviation of the 13C chemical shifts from the expected (mean) experimental value of the non-modified residue. As a proof-ofconcept, we used 13C chemical shifts, computed at the DFT-level of theory, to test this hypothesis. Moreover, as a validation test of this approach, we compare our theoretical computations of the 13Cε chemical-shift values against existing experimental data, obtained from NMR spectroscopy, for methylated and acetylated lysine residues with good agreement within ~1 ppm. Then, further use of this approach to select the most suitable 13C-nucleus, with which to determine other modifications commonly seen, such as methylation of arginine and glycosylation of serine, asparagine and threonine, shows encouraging results.